Clinicopathological profile of peritoneal tuberculosis and a new scoring model for predicting mortality: an international ID-IRI study - Tanoglu, Alpaslan; Erdem, Hakan; Friedland, Jon S.; Ankarali, Handan; Garcia-Goez, Jose Fernando; Albayrak, Ayse; Aypak, Adalet (Springer, 2023)
Existing literature about peritoneal tuberculosis (TBP) is relatively insufficient. The majority of reports are from a single center and do not assess predictive factors for mortality. In this international study, we investigated the clinicopathological characteristics of a large series of patients with TBP and determined the key features associated with mortality. TBP patients detected between 2010 and 2022 in 38 medical centers in 13 countries were included in this retrospective cohort. Participating physicians filled out an online questionnaire to report study data. In this study, 208 patients with TBP were included. Mean age of TBP cases was 41.4 +/- 17.5 years. One hundred six patients (50.9%) were females. Nineteen patients (9.1%) had HIV infection, 45 (21.6%) had diabetes mellitus, 30 (14.4%) had chronic renal failure, 12 (5.7%) had cirrhosis, 7 (3.3%) had malignancy, and 21 (10.1%) had a history of immunosuppressive medication use. A total of 34 (16.3%) patients died and death was attributable to TBP in all cases. A pioneer mortality predicting model was established and HIV positivity, cirrhosis, abdominal pain, weakness, nausea and vomiting, ascites, isolation of Mycobacterium tuberculosis in peritoneal biopsy samples, TB relapse, advanced age, high serum creatinine and ALT levels, and decreased duration of isoniazid use were significantly related with mortality (p < 0.05). This is the first international study on TBP and is the largest case series to date. We suggest that using the mortality predicting model will allow early identification of high-risk patients likely to die of TBP.
Keywords: Tuberculosis; Peritoneal tuberculosis; Immune-suppression; Treatment; Mortality